(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2022)
Fuzzy theory gives us a new way to look at the information. Humans use language tocommunicate with each other, which shows how smart they are. Fuzzy theory makes it easier to writecomputer code that makes sense. Fuzzy theory also has a human-machine language system. It helps tocalm people’s emotions and their interactions with computers.It’s because of rapid urbanisation andchanges, such as the breakup of the family system, the high level of education, job changes, and themigration of young people to cities and abroad, that the elders don’t pay attention to them. Elderlypeople have many personal, social, economic, physical and psychological problems because of thesethings, as well Adjusting to less strength and less health is also a problem. All of these change the rolesthey used to play in their home and society. They have a lot of time on their hands, which makes themfeel lonely, afraid, and sad. As of right now, this is one of the most important issues in India, which iswhy we chose this one to work on. If you want to talk about how random things are, you can call ituncertainty. Our lives are full of many unknowns, such as randomness and fuzziness. However, not all ofthe unknowns have been looked into. Human communication has a lot of unanswered questions. Olderpeople have a hard time communicating with younger people, which makes them unsure about how longthey will live. So they think they were rejected, abandoned, and not cared for. When people hear vaguewords, they can think of them in many different ways. While it may be misunderstood, it leads to newideas. When something isn’t clear there are two sides to it. It does not have any specific rules. So, fuzzytheory is a way to deal with the language of uncertainty. Fuzzy theory gives us a new way to processinformation. Humans use language that shows how much they know to communicate with other people.Fuzzy theory lets us write computer code that shows how we know things. Thus, fuzzy theory acts as abridge between humans and machine language. It helps to cut down on the friction between humans andmachines.